Answer: 0.7
Step-by-step explanation:
p(tail) + p(head) = 1
p(tail) = 1 - p(head)
p(tail) = 1 -0.3
p(tail) = 0.7
mark the brainliest plzz
Answer:
Q1. The estimated sum of the two people are between 40 and 55 years old.
Q2. The first person is between 10 and 15 years older.
Step-by-step explanation:
We are given Age Range's for 2 people. The first question is asking for the sum of the two people's ages. In this case we can just <u><em>add</em></u> the two minimum ages together and then the two maximum ages like so,
<u>min:</u> 25 + 15 = 40
<u>max:</u> 35 + 20 = 55
So the estimated sum of the two people are between 40 and 55 years old.
The second question asks how much older the First person is from the Second person. We can calculate this by <u><em>subtracting</em></u> both age ranges like so,
<u>min:</u> 25 - 15 = 10
<u>max:</u> 35 - 20 = 15
So the first person is between 10 and 15 years older.
I hope this answered your question. If you have any more questions feel free to ask away at Brainly.
To find the inverse of f(x), you solve for the independent variable, x, and then swap the variable labels. The reason for doing so is easily seen if one remembers what an inverse function really is. The inverse function will produce the opposite coordinate as the parent function. If f(x)=(x,y), f^-1(x)=(y,x), so the inverse function simply creates the inverse of all of the points that exist for f(x)...with that out of the way, let y=f(x), then:
y=1/(9x-2) (I am trying to decipher what you actually meant to type)
Multiply both sides by (9x-2)
y(9x-2)=1 divide both sides by y
9x-2=1/y add 2 to both sides
9x=1/y+2 which is equal to
9x=(1+2y)/y divide both sides by 9
x=(1+2y)/(9y) now switch labels...
y=(1+2x)/(9x)
f^-1(x)=(1+2x)/(9x)
Again, I am not sure that I understood what you meant to type for the equation... strictly as typed you actually have:
y=x/9-2 which can be written as:
y=(x-18)/9 multiply both sides by 9
9y=x-18 add 18 to both sides
9y+18=x then switch labels
y=9x+18
f^-1(x)=9x+18
The denominator must be made clear in this format by using () brackets, otherwise it is anyone's guess...
The value of X is is equal to 1
Answer:
yes it is.
x = 4 and y = -3
Step-by-step explanation:
Solve simultaneously using elimination method:
equation 1 - equation 2
3x + y = 9 equation 1
-2x + y = 5 equation 2
_________
x = 4
plug 4 into any of the 2 equations and solve for y.
3(4) + y = 9
12 + y = 9
12-12 + y = 9-12
y = -3